An Archaeology of the Interior Case Studies: The Archaeology of Obsolete Stairs - Istiani, Noor Fajrina Farah (Indonesian Journal of Visual Culture, Design, and Cinema, 2022)
This paper discusses the possibility of adopting the study of archaeology as known in cultural theory to redesign the obsolete interior architecture element. The archaeological discipline might offer a possibility to understand the interior element thoroughly through emphasizing the specific material characteristics and their correlation to the different periodical lifetimes of the context. The idea of the archaeology of an interior introduces well-recorded analysis and material experimentation in the physical translation of interior elements. The design process is mainly conducted by emphasizing the notion of "after use" and imagining the object's future to tackle the issue of the obsolete interior. This study becomes an essential basis for understanding the role of an interior architect in responding to the subject of the decayed interior from the other point of view by taking a personal stand for "use" and "after use" beyond the conventional idea of functional space. In the case study, this paper examined the idea of repurposing obsolete stairs as an archetype element through the physical and poetic approach of the object by taking one of the projects in Master interior architecture studio in Rotterdam. This practice aims to augment the material and generate the essential foundation for a design practice that could sensitively respond to the personal stand on the spatial design process.